A study of the solidification and stability mechanisms of heavy metals in electrolytic manganese slag-based glass-ceramics - Wang, Jiaqi; Han, Fenglan; Yang, Baoguo; Xing, Zhibing; Liu, Tengteng (Frontiers in Chemistry, 2022)
To better solve the waste pollution problem generated by the electrolytic manganese industry, electrolytic manganese slag as the main raw material, chromium iron slag, and pure chemical reagents containing heavy metal elements mixed with electrolytic manganese slag doping. A parent glass was formed by melting the slag mixture at 1250 ℃, which was, thereafter, heat-treated at 900 ℃ to obtain the glass-ceramic. The results from characterizations showed that the heavy metal elements in the glass-ceramic system were well solidified and isolated, with a leakage concentration at a relatively low level. After crystallization, the curing rates of harmful heavy metals all exceed 99.9%. The mechanisms of heavy metal migration, transformation, and solidification/isolation in glass-ceramic curing bodies were investigated by using characterization methods such as chemical elemental morphological analysis, transmission electron microscopy, and electron microprobe. The most toxic Cr and Mn elements were found to be mainly kept in their residual state in the glass-ceramic system. It was concluded that the curing mechanism of the heavy metals in a glass-ceramic can either be explained by the chemical curing induced by bonding (or interaction) during phase formation, or by physical encapsulation. Characterization by using both TEM and EPMA confirmed that Cr and Mn were mainly present in the newly formed spinel phase, while the diopside phase contained a small amount of Mn. Zn, Cd, and Pb are not found to be concentrated and uniformly dispersed in the system, which is speculated to be physical coating and curing.